Framing Media William Gamson dan Modigliani: Pemberdayaan Perempuan Dalam Film Charlie’s Angel - Maulidatus Naqqiyah (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2024)
This study analyzes the film Charlie’s Angels using Gamson and Modigliani’s media framing approach to explore how the film frames issues of gender, power, and female empowerment. By examining framing elements such as metaphors, catchphrases, and cultural symbols, this research finds that the film consciously constructs a narrative of female empowerment in response to modern social dynamics, particularly in the context of feminism. The film breaks down traditional gender stereotypes common in the action genre, positioning women as active and independent subjects without excessive sexualization. Additionally, the characterization of women in the film demonstrates that gender equality is not only a moral value but also holds strong commercial resonance. The analysis reveals that Charlie’s Angels effectively frames women as competent and empowered agents of change, creating a narrative that aligns with the growing trend of gender equality in contemporary media. This study concludes that the film's framing of female empowerment serves not only as entertainment but also as a response to cultural demands for stronger and more empowered female representation on screen.